Contingent self-esteem and vulnerability to depression: academic contingent self-esteem predicts depressive symptoms in students - Schöne, Claudia; Tandler, Sarah S.; Stiensmeier-Pelster, Joachim (Frontiers in Psychology, 2015)
Low self-esteem has been established as a vulnerability factor for depression. In line with recent research, we suggest that a full understanding of the role of self-esteem in depression requires consideration of contingent self-esteem as well. For most people, competence is an important source of self-esteem. Students in particular link their self-esteem to academic competence. To test the hypothesis that academic contingent self-esteem (aCSE) predicts depressive symptoms, two studies were conducted. Preceding the investigation of our hypothesis, the first purpose of Study 1 was to describe the development of aCSE, self-esteem level, and depressive symptoms in adolescence in a sample of German students aged 10–16 (N = 1888) in order to provide a foundation for further analyses. Then, to address the main question, age and gender differences in aCSE, self-esteem level, and depressive symptoms as well as their relations were investigated. The results show that (1) gender differences emerged after the age of 10/11. Girls scored higher on aCSE and depressive symptoms and lower on self-esteem level than did boys, and aCSE and depressive symptoms decreased and self-esteem level increased over time in boys, while the rather disadvantageous pattern in girls remained stable. (2) After controlling for self-esteem level and aCSE, the effects of gender and age × gender interaction on depressive symptoms disappeared, suggesting an influence of aCSE on depressive symptoms. (3) aCSE predicted depressive symptoms over and above self-esteem level. Since the results of Study 1 did not allow for causal conclusions, a longitudinal study (N = 160) was conducted to further investigate the causal role of aCSE. According to the diathesis-stress model, aCSE was expected to serve as a diathesis for developing depressive symptoms in the face of academic stress (daily hassles) during an academic semester at university. The results of Study 2 revealed that aCSE interacted with corresponding hassles to predict increases in depressive symptoms. High levels of academic stress led to increases in depressive symptoms only among students who strongly based their self-esteem on academic competence. Implications for prevention and intervention of depression are discussed.